2020
DOI: 10.1016/j.est.2019.101129
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil-based bio-PCM for energy efficient building applications: Multipurpose thermal investigation and life cycle assessment

Abstract: This study aims at investigating the potential use of a bio-based phase change material, i.e. expired palm oil from the food industry, as a more sustainable alternative to petrochemical-based organic PCMs. To this purpose, thermogravimetric analysis (TGA) and isoconversional methods (Starink and Miura-Maki methods) are applied and the main thermo-physical properties of the blend are investigated by means of differential scanning calorimetry (DSC) and extensive thermal monitoring in a controlled realistic envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Based on the thermal comfort (20 < T < 26 • C) of human beings [10], PCMs with melting temperatures of 20-32 • C are most suitable [11]. Several potential candidates can be classified as organic PCMs, such as paraffin (C 13 -C 24 ) [12], alkanes (n-hexadecane [13], n-octadecane [14]), an eutectic mixture of capric acid and lauric acid [5], fatty acid esters [15], bio-PCMs [16]; and inorganic PCMs such as salt hydrates (CaCl 2 •6H 2 O [9], LiNO 3 •3H 2 O [6]). Inorganic PCMs normally present higher latent heat storage capacity than organic PCMs; however, they have many application issues, such as super-cooling, phase segregation, and corrosiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the thermal comfort (20 < T < 26 • C) of human beings [10], PCMs with melting temperatures of 20-32 • C are most suitable [11]. Several potential candidates can be classified as organic PCMs, such as paraffin (C 13 -C 24 ) [12], alkanes (n-hexadecane [13], n-octadecane [14]), an eutectic mixture of capric acid and lauric acid [5], fatty acid esters [15], bio-PCMs [16]; and inorganic PCMs such as salt hydrates (CaCl 2 •6H 2 O [9], LiNO 3 •3H 2 O [6]). Inorganic PCMs normally present higher latent heat storage capacity than organic PCMs; however, they have many application issues, such as super-cooling, phase segregation, and corrosiveness.…”
Section: Introductionmentioning
confidence: 99%
“…These OPFs and OPTs can be used in various industries such as broom from palm fronds [40] and compressed medium density fibreboard (MDF) from OPT [41], whereas oil palm empty fruit bunches (OPEFB) are being utilized widely as a mulch for palm oil trees or processed fertilizer to promote soil fertility [42]. The lignocellulosic characteristic of oil palm residues such as (OPEFB) can be a good source of polymer reinforcement material, petrochemical-based matter as a building buffer creating thermal equilibrium [43,44] and reinforcing broom frond fibre from palm oil with concrete, which is economical and eco-friendly for building construction. In addition, processed palm kernel cake has been commonly used for animal feed given to cattle and chicken [45,46].…”
Section: Palm Oil Origin Products and By-products With Their Characteristics And Current Utilisationmentioning
confidence: 99%
“…The system boundaries that have been employed in LCA studies of PCMs in buildings have been frequently selected for manufacturing and disposal stages [154,155] with an addition of the operation stage [159] or plant cultivation, manufacture, and transport stages [161]. A study which compares raw, waste palm oils and paraffin [161] demonstrated that palm oil production generated the most negative impact on the resources, ecosystem, and human health (15.5, 170, and 103.9 mPt), which is significantly higher than the values of paraffin (37.6, 4.2, and 9.2 mPt). The above is explained by the high CO 2 emissions as well as land and water consumption needed for the plant cultivation.…”
Section: Life Cycle Assessmentsmentioning
confidence: 99%